Design and Simulation of a Grid-Connected Solar-Wind Hybrid Power System with Inverter and Power Quality Enhancement in MATLAB - Rao, T. V.; Subrahmanyam, K. B. V. S. R.; O. Aravind, O. Aravind; Bhavani, Y. Lavanya; Pavan Kumar, D. Sai; K. Harshith, K. Harshith; G. Viswanadh, G. Viswanadh (Journal of Neonatal Surgery, 2025)
This paper presents a comprehensive design and simulation of a grid-connected hybrid power system integrating solar and wind energy, developed using MATLAB/Simulink. In contrast to conventional off-grid systems, this study focuses on a grid-connected configuration that combines the DC output from a solar power plant with the DC converted from wind power generation. The wind energy is initially captured by a wind power plant, where the AC output is converted into DC through a rectifier. The DC output is then coupled with the solar power system to create a hybrid energy source. A DC-DC converter is used to regulate the combined output, which is subsequently fed to an inverter. The inverter's output is connected to the grid through a filter to improve power quality. The system ensures optimal energy transfer and harmonics reduction, enhancing the stability and efficiency of the power supplied to the grid. This design provides a sustainable solution for renewable energy integration into the existing grid infrastructure. Furthermore, the paper highlights the importance of power quality enhancement techniques and the role of filters in reducing Total Harmonic Distortion (THD) to meet grid compliance standards. The MATLAB simulation results demonstrate the feasibility and efficiency of the proposed system in a real-world scenario. The study serves as an extension of off-grid hybrid systems, offering valuable insights for the development of on-grid renewable energy solutions in MATLAB-based simulations.